Analysis of Congenital Postaxial Polydactyly of the Foot Using Magnetic Resonance Imagings. Issue 4 (16th October 2019) - Choi, Jun Young
Category: Midfoot/Forefoot Introduction/Purpose: We aimed to evaluate the magnetic resonance imaging (MRI) findings of congenital postaxial polydactyly of the foot. Methods: Three-hundred and forty-seven feet of 288 patients who underwent congenital postaxial polydactyly or polysyndactyly correction were divided into five subtypes according to the radiographic shapes of deformity origins (widened metatarsal head, bifid, fused duplicated, incompletely duplicated, or completely duplicated). MRIs were assessed to determine whether they unrevealed areas were fused or separated. MRI was also used to assess cases with radiographic phalangeal aplasia. Results: Huge variations were noted in MRIs. Fusion or separation at the base or head between original and extra digits were observed, and MRI effectively depicted phalangeal aplastic. Conclusion: MRI evaluations of congenital postaxial polydactyly of the foot are useful for determining the anatomical statuses which were not visualized by plain radiography.